Incidence, Mortality, and Risk Factors of COVID-19 in Nursing Homes - Alberto Arnedo-Pena; Maria Angeles Romeu-Garcia; Juan Carlos Gascó-Laborda; Noemi Meseguer-Ferrer; Lourdes Safont-Adsuara; Laura Prades-Vila; Matilde Flores-Medina; Viorica Rusen; Maria Dolores Tirado-Balaguer; Susana Sabater-Vidal; Maria Gil-Fortuño; Oscar Pérez-Olaso; et al. (MDPI AG, 2022)
During the period from March 2020 to January 2021, we performed an analysis of incidence, mortality, and risk factors of COVID-19 in nursing homes (NHs) in two health departments (HDs) of Castellon (Spain) 2021 through epidemiological surveillance and an ecological design. Laboratory-confirmed COVID-19 cases, cumulative incidence rate (CIR), and mortality rate (MR) of 27 NHs were collected. Information of residents, staff, and facilities was obtained by questionnaire. Multilevel Poisson regression models were applied. All NHs in the HDs participated with 2229 residents (median: 83 years old, 67.3% women) and 1666 staff. Among residents, 815 cases (CIR: 34.8 per 100) and 202 deaths (MR: 8.7 per 100, case fatality 21.0%) were reported and, among staff, 296 cases (CIR: 19.2 per 100) without deaths. Residents' CIR and MR increased with staff CIR, age of the building, residents/staff ratios, occupancy rate, and crowding index; CIR increased with private NH ownership, large NH size, large urban area, and the percentage of women residents; and MR was associated with residents' severe disabilities. In conclusion, several risk factors of COVID-19 incidence and mortality can be prevented by improving infection and quality controls, ameliorating residents/staff ratios, improving structural facilities, and increasing NH public ownership to avoid new outbreaks.